2013
DOI: 10.1002/ett.2644
|View full text |Cite
|
Sign up to set email alerts
|

Multihop compute‐and‐forward for generalised two‐way relay channels

Abstract: The compute-and-forward (CaF) relaying strategy recently proposed by Nazer and Gastpar has been proven to achieve significant improvements in 'computation rate' than conventional relaying strategies in the multiple-access channel. Although there have been some recent efforts on the implementations of CaF, to the best of our knowledge, there has been no published work that analyses the outage performance of CaF in the multihop two-way relay channel (MH-TRC). In this paper, we extend the original CaF strategy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Telemedicine has become increasingly integral to modern healthcare systems, offering solutions to challenges such as geographical barriers, limited access to specialized care, and the rising demand for healthcare services. Central to telemedicine is the ability to transmit biomedical signals accurately and securely, ensuring that healthcare providers receive the necessary data for informed decision-making regardless of the patient's location [1]. EEG, a technique for recording and analysing electrical activity in the brain, holds immense diagnostic and therapeutic potential across various medical domains, including neurology, psychiatry, and sleep medicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telemedicine has become increasingly integral to modern healthcare systems, offering solutions to challenges such as geographical barriers, limited access to specialized care, and the rising demand for healthcare services. Central to telemedicine is the ability to transmit biomedical signals accurately and securely, ensuring that healthcare providers receive the necessary data for informed decision-making regardless of the patient's location [1]. EEG, a technique for recording and analysing electrical activity in the brain, holds immense diagnostic and therapeutic potential across various medical domains, including neurology, psychiatry, and sleep medicine.…”
Section: Introductionmentioning
confidence: 99%
“…These decoding methods have been tuned for either the lowest symbol error rate or the shortest sequence, as appropriate. At high SNR, it was found that both optimization factors are asymptotically the same in their computational intensity and memory footprint, the MAP algorithm wasn't widely adopted until the Log-MAP variant was introduced as represented in equation (1). Operating in the logarithmic domain, Log-MAP offers improved numerical stability across a broader radius of probabilities.…”
Section: Introductionmentioning
confidence: 99%
“…However, the employment of relay doubles the required channels for the transmission from source to destination because of the half‐duplex constraint, which induces the spectral efficiency loss. To improve the spectral efficiency of relaying network, two‐way relaying (TWR) or bidirectional relaying, which employs the idea of network coding, was investigated in . In TWR, two terminals communicate bidirectionally via a half‐duplex relay, and the relay is allowed to combine the data from two opposite traffic flows to enhance the efficiency of single transmission.…”
Section: Introductionmentioning
confidence: 99%